2023
DOI: 10.1364/ol.486922
|View full text |Cite
|
Sign up to set email alerts
|

High-power, multi-junction, 905 nm vertical-cavity surface-emitting laser with an AlGaAsSb electron-blocking layer

Abstract: We report high-power multi-junction vertical-cavity surface-emitting lasers (VCSELs) with a significantly suppressed carrier leakage issue under high injection current and temperature. By carefully optimizing the energy band structure of quaternary AlGaAsSb, we obtained a 12-nm-thick AlGaAsSb electron-blocking layer (EBL) with a high effective barrier height (∼122 meV), a low compressive strain (∼0.99%), and a reduced electronic leakage current. The resulting three-junction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…National Chiao-Tung University conducted both theoretical and experimental investigations into the carrier blocking effect on 850 nm InAlGaAs/AlGaAs VCSELs [24]. Yun et al made further advancements by optimizing the energy band structure of quaternary AlGaAsSb [31]. An EBL with a thickness of 12 nm was developed using AlGaAsSb, exhibiting a high effective barrier height (∼122 meV), low compressive strain (∼0.99%), and reduced electronic leakage current.…”
Section: Carrier Blocking Layermentioning
confidence: 99%
See 1 more Smart Citation
“…National Chiao-Tung University conducted both theoretical and experimental investigations into the carrier blocking effect on 850 nm InAlGaAs/AlGaAs VCSELs [24]. Yun et al made further advancements by optimizing the energy band structure of quaternary AlGaAsSb [31]. An EBL with a thickness of 12 nm was developed using AlGaAsSb, exhibiting a high effective barrier height (∼122 meV), low compressive strain (∼0.99%), and reduced electronic leakage current.…”
Section: Carrier Blocking Layermentioning
confidence: 99%
“…These devices also exhibited a maximum SE of 5.4 W A −1 , approximately five times higher than that of traditional single-junction VCSELs with the same aperture size. Also, Yun et al reported on high-power MJ 905 nm VCSELs featuring a 12 nm thick AlGaAsSb EBL [31]. The 905 nm VCSEL with three junctions (3 J) and the suggested EBL demonstrated enhanced performance, with an increased maximum output power (∼46.4 mW) and PCE (∼55.4%) under RT operation.…”
Section: Mj-vcsel Device Engineeringmentioning
confidence: 99%